2002
DOI: 10.1038/417141a
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of the model actinomycete Streptomyces coelicolor A3(2)

Abstract: Streptomyces coelicolor is a representative of the group of soil-dwelling, filamentous bacteria responsible for producing most natural antibiotics used in human and veterinary medicine. Here we report the 8,667,507 base pair linear chromosome of this organism, containing the largest number of genes so far discovered in a bacterium. The 7,825 predicted genes include more than 20 clusters coding for known or predicted secondary metabolites. The genome contains an unprecedented proportion of regulatory genes, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
2,551
5
30

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 2,958 publications
(2,692 citation statements)
references
References 47 publications
48
2,551
5
30
Order By: Relevance
“…The large number of regulatory proteins that govern the gene expression in a temporal- and spatial-specific manner underscores this capability. It was reported that 965 regulation-related proteins are in the S. coelicolor genome, accounting for about 12% of the ORFs [3]. Our comparative analysis revealed that 263 gene families in the core genome are related to DNA-dependent regulation of transcription (GO:0006355), 201 of which may have sequence-specific DNA binding transcription factor activity (GO:0003700) and 43 families could have specific transcriptional repressor activity (GO:0016566).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The large number of regulatory proteins that govern the gene expression in a temporal- and spatial-specific manner underscores this capability. It was reported that 965 regulation-related proteins are in the S. coelicolor genome, accounting for about 12% of the ORFs [3]. Our comparative analysis revealed that 263 gene families in the core genome are related to DNA-dependent regulation of transcription (GO:0006355), 201 of which may have sequence-specific DNA binding transcription factor activity (GO:0003700) and 43 families could have specific transcriptional repressor activity (GO:0016566).…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, 303 gene families in the core genome are predicted to have transfersase activity (GO:0016740), constituting the most abundant class of the enzymes in the core genome. These statistics reflect the most distinctive characteristics of streptomycetes: a powerful biochemical machinery with a magnitude unusually large number for biosynthesis and biotransformation [3]. Table 2 lists examples of functional categories in the core genome critical for Streptomyces biology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations